2015 23rd European Signal Processing Conference (EUSIPCO) 2015
DOI: 10.1109/eusipco.2015.7362564
|View full text |Cite
|
Sign up to set email alerts
|

3D sound field analysis using circular higher-order microphone array

Abstract: This paper proposes the theory and design of circular higher-order microphone arrays for 3D sound field analysis using spherical harmonics. Through employing the spherical harmonic translation theorem, the local spatial sound fields recorded by each higher-order microphone placed in the circular arrays are combined to form the sound field information of a large global spherical region. The proposed design reduces the number of the required sampling points and the geometrical complexity of microphone arrays. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Samarasinghe et al [15] developed a regularized leastsquares inverse interpolation approach based on spherical harmonic translation coefficients using an array of HOA microphones. Several subsequent studies have demonstrated or improved upon this method [16][17][18]. In particular, Ueno et al [19] developed a similar method that takes a Bayesian inference approach, which was shown to achieve improved performance (in terms of reconstruction errors) at high frequencies.…”
Section: Linear Methodsmentioning
confidence: 99%
“…Samarasinghe et al [15] developed a regularized leastsquares inverse interpolation approach based on spherical harmonic translation coefficients using an array of HOA microphones. Several subsequent studies have demonstrated or improved upon this method [16][17][18]. In particular, Ueno et al [19] developed a similar method that takes a Bayesian inference approach, which was shown to achieve improved performance (in terms of reconstruction errors) at high frequencies.…”
Section: Linear Methodsmentioning
confidence: 99%
“…Approaches based on HOA representations include extrapolation-based algorithms [6][7][8][9][10], which extrapolate a finite set of spatial parameters based on measured RIRs and thus allow the RIR to be synthesized outside the region covered by microphones. While such extrapolation approaches can introduce inaccurate source localization and audible processing artifacts, such as spectral coloration [11], a number of interpolation-based approaches using HOA microphone array recordings are prone to mitigate these effects, such as the regularized least-squares interpolation approaches using spherical harmonic translation coefficients [12][13][14][15]. More recent related work [16,17] utilized frequency-dependent regularization to limit spectral variation and exclude any microphones closer to a sound source than to the target listening position in order to obtain accurate results for near-field sources.…”
Section: Introductionmentioning
confidence: 99%